(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Result of studying a nutrition value of main communities in grasslands is depending on ecological zones and growth stage. Contamination of non essential elements, macro-micro element is non-significant difference between forest steppe and steppe while a significant difference came out in semi desert area. Journal of agricultural sciences №15 (02): 113-117, 2015